Minto Songs ... - Tuttle, Siri; Tuttle, Siri (unknown, 2010)
Among the cultural objects gathered in the last century from indigenous groups in the Americas is a large amount of recorded song. Among Alaskan Athabascans, song serves as a community-internal activity that supports native language use and cultural revitalization, and also as a marker of village identity in the larger communities. The Minto Athabascan community in Alaska is the last village that has speakers of the Lower Tanana Athabascan language, and it has a very strong song tradition. We propose to organize the Minto song data available to us (Alaska Native Language Center @ UAF; Polar Regions collections at Rasmuson Library, and in the Rooth & Lundstrom collections in Sweden) and to make it usable by community members by creating web-ready multimedia pages that can be added to existing websites and controlled by the Village of Minto. Annotations for songs will be recorded with Minto elders who can identify the composers and occasions for which the songs were composed. ...